EFFECT OF POLYETHYLENE GLYCOL (PEG) AND PLANTING METHODS ON SWEET CORN PRODUCTIVITYEFFECT OF POLYETHYLENE GLYCOL (PEG) AND PLANTING METHODS ON SWEET CORN PRODUCTIVITY - A Abou El-Yazied; I El-Oksh; Rawia, El-Bassiouny; Manal Attia (Arab Universities Journal of Agricultural Sciences, 2007)
This study was conducted in loamy soil at Qaha Experimental Station, Horticulture Research Institute, ARC, Kalubia governorate, during 2002/2003 and 2003/2004 seasons to study the effect of PEG and planting methods on sweet corn productivity. The obtained results indicated that GSS 9377 F1 hybrid plants produced vigorous growth and higher early and total yield than those of Endeavor F1 hybrid. Direct seeding in the open field or under tunnels increased plant height, stem diameter, number of leaves/plant, plant fresh weight, unhusked ear weight, husked ear weight and total yield compared to transplanting methods. Transplanting produced the higher early yield ei-ther with open field or under tunnels. Primed seeds of sweet corn F1 hybrids (GSS 9377 and Endeavor) in PEG 6000 dalton for 6 hours at the concentration of 400 g/L produced taller plants with thicker stem diameter, higher number of leaves/plant and greater fresh weight, higher un-husked and husked ear weight, ear length, higher TSS as well as early and total yield compared to check untreated seeds